GbCYP86A1‐1 from Gossypium barbadense positively regulates defence against Verticillium dahliae by cell wall modification and activation of immune pathways - Wang, Guilin (Plant Biotechnol J, 2019)
Suberin acts as stress‐induced antipathogen barrier in the root cell wall. CYP86A1 encodes cytochrome P450 fatty acid ω‐hydroxylase, which has been reported to be a key enzyme for suberin biosynthesis; however, its role in resistance to fungi and the mechanisms related to immune responses remain unknown. Here, we identified a disease resistance‐related gene, GbCYP86A1‐1, from Gossypium barbadense cv. Hai7124. There were three homologs of GbCYP86A1 in cotton, which are specifically expressed in roots and induced by Verticillium dahliae. Among them, GbCYP86A1‐1 contributed the most significantly to resistance. Silencing of GbCYP86A1‐1 in Hai7124 resulted in severely compromised resistance to V. dahliae, while heterologous overexpression of GbCYP86A1‐1 in Arabidopsis improved tolerance. Tissue sections showed that the roots of GbCYP86A1‐1 transgenic Arabidopsis had more suberin accumulation and significantly higher C16‐C18 fatty acid content than control. Transcriptome analysis revealed that overexpression of GbCYP86A1‐1 not only affected lipid biosynthesis in roots, but also activated the disease‐resistant immune pathway; genes encoding the receptor‐like kinases (RLKs), receptor‐like proteins (RLPs), hormone‐related transcription factors, and pathogenesis‐related protein genes (PRs) were more highly expressed in the GbCYP86A1‐1 transgenic line than control. Furthermore, we found that when comparing V. dahliae ‐inoculated and noninoculated plants, few differential genes related to disease immunity were detected in the GbCYP86A1‐1 transgenic line; however, a large number of resistance genes were activated in the control. This study highlights the role of GbCYP86A1‐1 in the defence against fungi and its underlying molecular immune mechanisms in this process.